2007
DOI: 10.1080/00103620701380488
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phytoremediation of Chromium‐Contaminated Soils by Fenugreek, Spinach, and Raya

Abstract: A glasshouse investigation was undertaken to evaluate the natural potential of fenugreek (Trigonella foenumgraecum L.), spinach (Spinacia oleracea L.), and raya (Brassica campestris L.) for cleanup of chromium (Cr)-contaminated silty loam and sandy soils. Four kilograms of soil per treatment in earthen pots was treated with five levels of chromium [0, 1.25, 2.5, 5.0, and 10.0 mg Cr kg 21 soil through dipotassium chromate (K 2 Cr 2 O 7 ], equilibrated for 21 days at field-capacity moisture content, and then fen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 24 publications
1
23
0
1
Order By: Relevance
“…Under these conditions, plant growth and biomass are negatively affected [17][18][19][20]. According to Caldelas et al (2012) [19], not only growth inhibition happened, but also root to shoot dry matter partitioning (R/S) modified (increased 80%) at Cr toxic conditions in Iris pseudacorus L. plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, plant growth and biomass are negatively affected [17][18][19][20]. According to Caldelas et al (2012) [19], not only growth inhibition happened, but also root to shoot dry matter partitioning (R/S) modified (increased 80%) at Cr toxic conditions in Iris pseudacorus L. plants.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoremediation is an emerging technology and is considered for remediation of inorganic-and organic-contaminated sites because of its cost-effectiveness, aesthetic advantages, and long-term applicability. This technique involves the use of the ability of some plant species to absorb and accumulate high concentrations of heavy metal ions [17]. Some of these species may be a few ones from Brassicaceae family, such as raya (Brassica campestris L.) [17] and Thlaspi caerulescens [23], or from other families, such as spinach (Spinacia oleracea L.) [17], Sedum plumbizincicola [24], Amaranthus hypochondriacus [25], Eremochloa ophiuroides [26], Iris pseudacorus L. [19], Ricinus communis L., plant of Euphorbiaceae family [18].…”
Section: Introductionmentioning
confidence: 99%
“…From the above result it is also concluded that metal accumulation is higher in roots as compare to shoots. On the contrary, Dheri et al (2007) reported maximum removal of hexavalent chromium 42% through spinach 72 (Spinacea olaracea). The chromium uptake by plants has been found to be positively correlated to chromium application by many workers (Cervantes et al, 2001;Babalola et al, 2008;Singaram, 1994;Singh, 2001;Jain et al, 2000;Negi et al, 2007;Karunyal et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…From the above result it is also concluded that metal accumulation is higher in roots as compare to shoots. On the contrary, Dheri et al (2007) reported maximum removal of hexavalent chromium 42% through spinach …”
mentioning
confidence: 95%
“…Earlier investigations were reported on growth of fenugreek on chromium-contaminated soil Dheri et al, 2007 . Agriculture soil was sterilized before the experiments to ensure no interference from other microorganisms Anuradha et al, 2014 .…”
Section: Germination Trials Using Trigonellafoenum-graecum Fenugreekmentioning
confidence: 99%